The Effectiveness of the Community Medicine Undergraduate Program in Medical Schools on Enabling Medical Graduates to Work in the Health Systems - Hossein Jabbari Bayrami; Abolgasem Amini; Fariba Bakhshian; Mohammad zakaria Pezeshki; Mehrangiz Gasemiyeh; Javaher Yari (Tabriz University of Medical Sciences, 2013)
Introduction: The main mission of medical schools is to train competent medical trainees for providing primary health care services, management of health care team and improving the health status of the population. The aim of this study was to determine the effectiveness of the undergraduate program of community medicine department among the graduates as general (family) physicians in health system of East Azerbaijan, North-West of` Iran. Methods: In this cross- sectional study all family physicians of East Azerbaijan province were included. A questionnaire on the views of graduates about the effectiveness of community medicine undergraduate program was used for gathering data. Data were analyzed by T-test, ANOVA, and Pearson correlation. Results: Performance of community medicine department in creating competency for providing effective health services among physicians was 2.13 and management competency was 1.96 out of 4. To teach the necessary skills to meet the professional needs in Primary Health Care (PHC), Tabriz Community Medicine Department was better compared to Azad and other medical schools (p<0.001). Conclusions: The results of the study showed that the community medicine program in undergraduate medical education was effective for future career of physicians in the health system. There is a need to revise the health management courses in community medicine program.